(untitled) (Journal of Global Accounting, 2023)
This work examined the relationship between direct pay and the expansion of organization as proxies of rewards and organizational performance. Descriptive design was adopted in the execution of the study. All participants of the studied firm had a fair chance of being included with a quota sampling technique. The sample size was 196 out of a population of 384 staff of International Breweries PLC. Data was collected with structured 5 point Likert-Scaled instrument whose validity and reliability was confirmed based on a pilot test that yielded 0.84 from Crombach Alpha Correlation Coefficient. Descriptive statistics were employed to arrive at findings. The result the study showed that direct pay have positive relationship with business expansion. This Study therefore concludes that direct pay has positive and critical effect on business expansion of firms and recommends that firms should adopt reward and incentive systems that deliver direct pay to the employees to enhance performance and growth.